Identification and validation of an excellent prognosis subtype of muscle-invasive bladder cancer patients with intratumoral CXCR5+ CD8+ T cell abundance. (1st January 2020) - Huang, Qiuren; Zhou, Quan; Zhang, Hongyu; Liu, Zhaopei; Zeng, Han; Chen, Yifan; Qu, Yang; Xiong, Ying; Wang, Jiajun; Chang, Yuan; Xia, Yu; Wang, Yiwei; et al.
ABSTRACT: Bladder cancer is the ninth most frequent-diagnosed disease worldwide, bearing high morbidity and mortality rates. Studies have shown that a particular population of CXCR5 + CD8 + T cells was associated with superior prognosis in various tumor types, and yet its role in muscle-invasive bladder cancer (MIBC) remains unclear. In this study, 662 MIBC patients from 3 cohorts (Zhongshan Hospital, n = 141; Shanghai Cancer Center, n = 108; The Cancer Genome Atlas, n = 403) were analyzed retrospectively. 11 fresh resected samples of MIBC were examined to characterize the phenotype of CXCR5 + CD8 + T cells and 402 MIBC patients from TCGA were applied for bioinformatics analysis. It was explored that the abundance of intratumoral CXCR5 + CD8 + T cells indicated superior overall survival and disease-free survival. Patients with a higher infiltration of CXCR5 + CD8 + T cells in tumor tissue benefit more from adjuvant chemotherapy (ACT). Intratumoral CXCR5 + CD8 + T cells displayed cytolytic and self-renewal features. Remarkably, CXCR5 + CD8 + T cells were mainly presented in the basal and stromal-rich subtypes of MIBC and tumors with enriched CXCR5 + CD8 + T cells showed limited FGFR3 signaling signature and activated immunotherapeutic and EGFR associated pathway. In conclusion, we identified an excellent prognosis and ACT sensitive subtype of MIBC with intratumoral CXCR5 + CD8 + T cell abundance. Tumors with high density of CXCR5 + CD8 + T cells possessed potential sensitivity to immunotherapy and EGFR-targeted therapy. CXCR5 + CD8 + T cells provide a new potential biomarker as well as a therapeutic target in MIBC.